Comportamiento en ambientes de diversos niveles de productividad de genotipos de frijol negro desarrollados en Colombia - Voysest Voysest, Oswaldo (International Center for Tropical Agriculture, 1982)
The genetic changes occuring in av. productivity, adaptation, and response to environments with different levels of yield for black-colored grain material selected by CIAT during 1976-79 are examined. Data from 124 expt. of the International Bean Yield and Adaptation Nursery (IBYAN) of black beans, conducted at 80 sites in 20 countries, were used in a randomized complete block design with 4 replications in 1976 and 1977 and 3 replications in 1978 and 1979. Var. Jamapa, Porrillo Sintetico, and ICA Pijao were used as international checks to estimate the av. increase in yield of the tested lines; the coefficient of regression (bi), the coefficient of determination (r2), and the standard deviation of regression (Sd) were estimated by a simple linear regression analysis and the component of genotype/environment interaction (o2GA) was measured by the Plaisted methodology, successively omitting one of the lines. Av. yields of the 5 best lines were higher than the av. of international checks by 1-22 percent. The range of bi varied between 0.84-1.08 and 0.93-1.17 for high-and low-yielding lines, resp. In the exptl. lines, a high correlation of the S2d and o2 parameter array was found. The highest yielding lines showed b values closer to those of Porrillo Sintetico (equal to or less than 1) than those of Jamapa (equal to or greater than 1). High correlation of b with the ranges of yield variation of cv. (considered individually or in general) ainong select and nonselect environments, allows the response of the lines to environments with different levels of productivity to be estimated. Results of analyses are discussed and summarized in table form. (CIAT)